2017
DOI: 10.21521/mw.5768
|View full text |Cite
|
Sign up to set email alerts
|

Influence of bisfenol A on chemical coding of the nerve fibers of the cardiac apex in the domestic pig

Abstract: Influence of bisfenol A on chemical coding of the nerve fibers of the cardiac apex in the domestic pig

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 37 publications
3
8
0
Order By: Relevance
“…The knowledge of the influence of BPA on the peripheral nervous system is more limited than on the central nervous system. It is known that BPA inhibits the voltage-gated sodium channels in dorsal root ganglia and may change the neurochemical characterization in autonomic nervous structures supplying various internal organs [ 60 , 88 , 89 , 90 , 91 ]. The decrease in total number of neurons noted in the present study under the impact of BPA also confirms neurotoxic properties of this substance.…”
Section: Discussionmentioning
confidence: 99%
“…The knowledge of the influence of BPA on the peripheral nervous system is more limited than on the central nervous system. It is known that BPA inhibits the voltage-gated sodium channels in dorsal root ganglia and may change the neurochemical characterization in autonomic nervous structures supplying various internal organs [ 60 , 88 , 89 , 90 , 91 ]. The decrease in total number of neurons noted in the present study under the impact of BPA also confirms neurotoxic properties of this substance.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown a link between excessive exposure to BPA and various civilization diseases, including diabetes, hypertension, heart attack, or neoplasms [ 31 ]. Moreover, it is known that BPA changes the neurochemical characterization of neurons and nerves within the peripheral nervous system in various internal organ including intestine, heart, and liver [ 32 , 33 , 34 , 35 ], but until now the participation of NRG-1 in mechanisms connected with BPA intoxication has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…They were fed twice a day with commercial standard feed for piglets and had unlimited access to drinking water. The animals’ care during the experiment was previously described by Makowska et al [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Other studies have shown that BPA intensifies atherosclerosis processes in the cardiovascular system [ 15 , 16 ] and oxidative stress reactions in cardiomyocytes [ 17 ]. In turn, the authors’ previous study showed that BPA in high doses affects the neurochemical characterization of nerves located in the heart wall [ 18 ]. Moreover, it is known that BPA increases the risk of perimyocarditis and fibrosis after viral infections [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation